Impact of the establishment of the oil palm plantations to socio economy of the villagers in Kranggas, Pantu, Sri Aman - Dickens, Mambu (Universiti Malaysia Sarawak (UNIMAS, 2013)
(This study is conducted to evaluate the socioeconomic impact of the land development by the Land Custody and Development Authority (LCDA) for oil palm plantation on the participating communities in Kranggas, Pantu District, Sri Aman. The plantation company, namely Winsome Pelita Patu (Kranggas Estate) Sdn Bhd, is a state government selected investor responsible to develop oil palm plantation in the study area. This project is a Joint Venture project between the investor, Land Custody and Development Authority (LCDA) as a state managing agent and the landowner In order to obtain feedback from the community on the impact of oil palm development project to the community in the area, the heads of the households of all the 39 bileks in the three longhouses (Rh Tana, Rh Mordi and Rh Jeni) in Kranggas had been interviewed face-to-face by using the structured questionnaire. The findings of the study show that there was a significant positive change of the livelihood of the community in Kranggas after the establishment of the oil palm plantation in the area. These changes include increase in households' income, improved opportunity for the community due to the improved facilities provided in the area such as the construction of roads that has connected Kranggas to the Serian-Sri Aman main road which has enabled villagers to better access to health and educational services. Overall, the findings of the study show that the socio-economy of the community in Kranggas, Pantu, Sri Aman has improved after the establishment of oil palm plantation in the area. It is therefore suggested that this successful model would be adopted in other areas to improve the standard of living of the people particularly those in other rural areas